New models and algorithms for RNA pseudoknot order assignment - Zok, Tomasz; Badura, Jan; Swat, Sylwester; Figurski, Kacper; Popenda, Mariusz; Antczak, Maciej (Zielona Góra: Uniwersytet Zielonogórski)
The pseudoknot is a specific motif of the RNA structure that highly influences the overall shape and stability of a molecule. It occurs when nucleotides of two disjoint single-stranded fragments of the same chain, separated by a helical fragment, interact with each other and form base pairs. Pseudoknots are characterized by great topological diversity, and their systematic description is still a challenge. In our previous work, we have introduced the "pseudoknot order": a new coefficient representing the topological complexity of the pseudoknotted RNA structure. It is defined as the minimum number of base pair set decompositions, aimed to obtain the unknotted RNA structure.
Keywords: RNA pseudoknot order; conflict graph; vertex coloring; maximum independent set; integer programming